COMPUTER TECHNOLOGIES AS A MEANS OF ORGANIZING INDEPENDENT WORK - Rozanna Abdullaeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article discusses the features of computer technology used as a means of organizing independent work. The use of information and computer technologies in the training of future medical workers can effectively solve a number of problems associated with the uniqueness of the professional activity of physicians. A description is given of information and computer technologies used to create, in the form of computer hardware, software, cellular communications, e-mail, wireless and cable communications networks, and multimedia tools.